Flood Control with the Shortcut Method on Drainage Channels in the Kampar District Police Area - Randhi Saily; Desi Yasri; Erna Agnesa (Formosa Journal of Multidisciplinary Research, 2022)
Kampar Regency, especially the Polres area, is an area that often experiences stagnant water when it rains with high intensity and long duration. The existing drainage condition is not sufficient to accommodate rainwater runoff. The purpose of this research is to review the hydrological aspects and the capacity of the drainage canals that cause inundation in Kampar Regency, as well as to design and determine the location for the construction of a directional drainage (Short-cut). Rain data used is the last 10 years. The design rain is calculated based on the analysis of the frequency distribution of the log person type III method. The research results show that Qcapacity > Runoff. The design channel length is 190 meters with a 1000x1200 u-ditch drainage type.